Heidi Heckelbeck and the lost library book - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2021)
Heidi has an overdue adventure when she loses a library book in this thirty-second Heidi Heckelbeck adventure! The Brewster Library has always been a magical place for kids in town. It has a story waiting for everyone. But imagine Heidi's surprise when Aunt Trudy lets her in on a well-kept secret: the Brewster Library has a real magic section! When Heidi checks out a title for a special project, she learns that you can't always judge a book by its cover. Especially when it's a bewitched book that loves to play pranks. With easy-to-read language and illustrations on almost every page, the Heidi Heckelbeck chapter books are perfect for beginning readers.